Factors of Transport (and Logistic) Development - Trupac, Igor (Promet - Traffic&Transportation, 2003)
The characteristic of the present time is the crucia significant,and rapid transformation of the common conditions oftrade, transport, and information interchange. However, thestrategic role in this process belongs to the communication andinformation systems. The development of communication andinformation technology systems is incredibly fast, so that referenceis made to the world of advanced communications.The trend found in business life is very complicated. We arestriving both towards collectivisation as well as individualisationat the same time, since thus the world of competitivenessand co-operation is created.In this world the transport and communication and informationnetwork is expected to become fully integrated in the industrialproduction and service-providing system, so as to providethe foundation for a dynamic adjustment to the market requirements.It is clear that the transport infrastructure and cross-borderdevelopment stand for the predominant developmental impulseto the general and physical development of particular areasand of the Slovenian country as a whole. In the pre-accessionperiod of Slovenia to the EU (the accession of Slovenia tothe EU could only occur in 2003-2004, at the earliest), it is necessary,in both fields, to accelerate the activities that will provideco-operation on equal footing. Taking into consideration allthe increasingly open borders (associated members, full members),the economic development will have a favourable impacton the improved competitiveness and co-operation among regionsand states, which will result in an increase in the flow ofgoods, capital and services, and in particular in an improvedmobility of the population.